Web of Change: Exploring the Internet’s Influence on Education, Healthcare, Business, the Environment, and Democracy - Gaius ILIYA; Bisallah I. HASHIM (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
The Internet has profoundly transformed our lives, introducing revolutionary changes in how we learn, work, and connect with one another. This comprehensive paper delves into the impact of internet applications on key societal domains, namely education, healthcare, business, the environment, and democracy. While exploring these critical areas, it is important to note that this study primarily focuses on internet applications’ influence in terms of expanding access to education and healthcare, optimizing business operations, and fostering democratic engagement. Other facets of the internet, such as entertainment, news, and communication (chatting), though significant, have not been extensively explored within the scope of this research. Through a meticulous analysis of the subject matter, this paper reveals the positive implications of internet applications, including enhanced educational and healthcare accessibility, improved business efficiency, and increased democratic participation. However, it also acknowledges the potential drawbacks, such as the spread of misinformation and privacy concerns. This research emphasizes the need for continued inquiry and dialogue to fully comprehend and harness the immense potential of internet applications in shaping our society.